Firms’ wage policies: New evidence from linked employer-employee data - Suleman, F. (2013)
The research on wage policies has been triggered by the interest in identifying whether labour market or institutional forces shape the wage settings inside firms. This paper draws on linked employer-employee data and uses a fuzzy c-means clustering analysis to identify typical wage policies of medium and large firms in Portugal. Empirical evidence suggests that firms are segmented into four clusters that can be labelled according to wage rules as “Regulated”, “Asymmetric”, “Hierarchical” and “Discretionary”. The first two clusters comprise low wage firms, and are highly responsive to market conditions. The firms belonging to the latter clusters take advantage of discretionary power to differentiate the workforce. Our findings therefore illustrate different dimensions of wage flexibility. Furthermore, we found that employment flexibility and wage adjustments can coexist, and affects female, young, and blue collar workers in particular.